1975
DOI: 10.1111/j.1755-3768.1975.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Applanation Tonometry and Central Corneal Thickness

Abstract: Readings with the Goldmann applanation tonometer were made at various intraocular hydrostatic pressures and compared with central corneal thickness and radius in rabbit and in man. Linear correlations were established between hydrostatic pressure and applanation readings, with correlation coefficients close to 1.0. In rabbits the tonometer readings were generally too low. In human eyes with a normal corneal thickness tonometer readings and hydrostatic pressure coincided, with thick corneas the readings were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
443
4
35

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 809 publications
(495 citation statements)
references
References 6 publications
13
443
4
35
Order By: Relevance
“…46 It is well known that thicker cornea in non-surgical patients causes an overestimation of IOP measured by applanation tonometry. [47][48][49] However, as the measurements compared preoperative with postoperative IOP for each individual patient rather than the mean between groups, the corneal pachymetry will have a lesser role in the variability of the values.…”
Section: Discussionmentioning
confidence: 99%
“…46 It is well known that thicker cornea in non-surgical patients causes an overestimation of IOP measured by applanation tonometry. [47][48][49] However, as the measurements compared preoperative with postoperative IOP for each individual patient rather than the mean between groups, the corneal pachymetry will have a lesser role in the variability of the values.…”
Section: Discussionmentioning
confidence: 99%
“…GAT measured IOP accurately when CCT was 520 mm, and each 10% difference of CCT would result in 1.1 mm Hg differences in IOP. [18][19][20] In this study, the correlation between CH and IOPcc was also searched. There was a positive correlation and this is statistically significantly different (Pearson correlation test, r ¼ 0.466, Pr0, 05).…”
Section: Discussionmentioning
confidence: 99%
“…5 It is well known that GAT is affected by the central corneal thickness (CCT). 6,7 The Ocular Hypertension Treatment Study showed that CCT is an important and independent risk factor for the progression of ocular hypertension to a first diagnosis of glaucoma. 8 It has been estimated that a measurement error of between 0.11 9 and 0.71 mmHg 7 occurs per 10 mm deviation from the average CCT of 550 mm.…”
Section: Introductionmentioning
confidence: 99%